2022
DOI: 10.1039/d2ta05332b
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced photocatalytic overall water-splitting over Au nanoparticle-decorated CaNb2O6 electrospun nanofibers

Abstract: Design and construction of wide-bandgap semiconductor nanostructures is a promising way to achieve the photocatalytic overall water-splitting, because their redox potentials are easy to simultaneously satisfy thermodynamic requirements of water...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In order to further discuss the high activity of [Cu 20 ] in catalyzing the cycloaddition reaction of CO 2 and epoxides, since the interaction between epichlorohydrin and the metal sites played a key role in the reaction mechanism, the adsorption energies of both clusters with epichlorohydrin were calculated by the DFT method. 65–68 DFT calculation results demonstrated that the epichlorohydrin adsorption active sites were mainly attributed to the unsaturated Cu site in the [Cu 20 ] or [Cu 2 ] cluster (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further discuss the high activity of [Cu 20 ] in catalyzing the cycloaddition reaction of CO 2 and epoxides, since the interaction between epichlorohydrin and the metal sites played a key role in the reaction mechanism, the adsorption energies of both clusters with epichlorohydrin were calculated by the DFT method. 65–68 DFT calculation results demonstrated that the epichlorohydrin adsorption active sites were mainly attributed to the unsaturated Cu site in the [Cu 20 ] or [Cu 2 ] cluster (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…c Moles of cyclic carbonate per mole of catalyst [Cu 20 ]. d Moles of cyclic carbonate per mole of catalyst [Cu 20 ] per hour.both clusters with epichlorohydrin were calculated by the DFT method [65][66][67][68]. DFT calculation results demonstrated that the epichlorohydrin adsorption active sites were mainly attributed to the unsaturated Cu site in the [Cu 20 ] or [Cu 2 ] cluster (Fig.3).…”
mentioning
confidence: 99%
“…[1,[3][4][5][6] Thus, loading cocatalysts is now a common strategy to promote catalytic activity and reaction rates for the HER. [7,8] Noble metallic cocatalysts, such as Pt, Pd, Ru, or Au, are ideal cocatalysts in terms of their high efficiency in the HER, but their expensive price and resource scarcity hinder their widespread implementation. It is of great significance to exploit noble-metal-free and earth-abundant alternatives suitable for various circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the poor photocatalytic efficiency arising from the high carrier recombination rates has always been a problem in photocatalytic appli-cations. To address this problem, numerous strategies have been adopted, including defect engineering, [10][11][12] precious metal modification, 13,14 ion doping 15,16 and heterojunction structures. 17 Despite much effort, the improvement in photocatalytic efficiency is still limited by the material synthesis procedures, material stability, and low quantum efficiency to some extent.…”
Section: Introductionmentioning
confidence: 99%